Evaluation of the Effects of Chamomill Mouthrinse on Recurrent Aphthous Stomatitis - S. Sahba (Frontiers in Dentistry, 2005)
Statement of Problem: Recurrent aphthous stomatitis (RAS) is one of the most common diseases affecting the oral mucosa. Many topical and systemic medications used to treat RAS have adverse local and systemic effects. Chamomill (kamillosan) has been shown to be an effective drug, without any noticeable side effects. Purpose: The aim of present study was to assess the efficacy of a chamomill mouthrinse on RAS in comparison with a placebo mouthrinse. Materials and Methods: The study was designed as a double blind randomized placebo controlled clinical trial with participation of 50 patients diagnosed with RAS. They were randomly divided into two groups: 26 patients forming the test group, received chamomill mouthrinse and 24 patients constituting the control group received a placebo rinse. All subjects were instructed to use the solutions three times a day until complete resolution of the lesions. Treatment outcome was assessed on days 3 and 5 and at the exact healing time. The ability of the solution to control the pain and burning sensation and the diameter of the ulcers was evaluated. Statistical analysis was performed using the 2 and unpaired t test for comparison between the two groups. Results: The chamomill group showed a significant reduction in the time required for controlling the pain and burning sensation (P